The Implementation Of Dynamic Governance In Increasing Local Revenue Of West Java Province - Sarihati , Tati; Fitriany, Dea Nur (Dinasti Research, 2025)
This study aims to analyse the application of Dynamic Governance in increasing West Java Province's Regional Original Revenue (PAD), with a focus on the 2025 motor vehicle tax bleaching program. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation which are analysed using the data triangulation method. The analytical framework refers to the Dynamic Governance theory (Neo & Chen, 2007: 12-46) with three main dimensions: Thinking Ahead, Thinking Again, and Thinking Across. The results show that data-based fiscal planning, real-time policy evaluation, and cross-sector collaboration have succeeded in encouraging the optimisation of PAD revenue. The motor vehicle tax bleaching programme is proven to increase public participation and foster legal awareness in paying taxes, despite administrative challenges and the risk of future policy dependency. This research concludes that the Dynamic Governance approach is relevant in building adaptive, collaborative, and sustainable local fiscal governance.